2009
DOI: 10.1093/sw/54.3.195
|View full text |Cite
|
Sign up to set email alerts
|

Racial Minorities Then and Now: The Continuing Significance of Race

Abstract: Reading is a hobby to open the knowledge windows. Besides, it can provide the inspiration and spirit to face this life. By this way, concomitant with the technology development, many companies serve the e-book or book in soft file. The system of this book of course will be much easier. No worry to forget bringing the racial minorities then and now the continuing significance of race guest editorial book. You can open the device and get the book by on-line.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…Initially, the students found it difficult to conceptualize how cultural, language, social, economic, and religious dynamics complicated the panelists' access to health services. The students shared that discovering the continuing significance of race (Schiele & Hopps, 2009) and exploring their white privilege were uncomfortable, unanticipated 'excursions' on this journey (Pewewardy, 2007). They were overwhelmed by the immigrants' painful narratives and perceptions of being `trapped,' `discounted,' and 'misinformed' while attempting to negotiate health care services in the community.…”
Section: Gather Information On Community Dynamicsmentioning
confidence: 99%
“…Initially, the students found it difficult to conceptualize how cultural, language, social, economic, and religious dynamics complicated the panelists' access to health services. The students shared that discovering the continuing significance of race (Schiele & Hopps, 2009) and exploring their white privilege were uncomfortable, unanticipated 'excursions' on this journey (Pewewardy, 2007). They were overwhelmed by the immigrants' painful narratives and perceptions of being `trapped,' `discounted,' and 'misinformed' while attempting to negotiate health care services in the community.…”
Section: Gather Information On Community Dynamicsmentioning
confidence: 99%
“…Student activists, many of whom were students of color, pushed for a more relevant curriculum and diverse faculty. Some professors made alliances with the poor and found pathways to help change the social work academic establishment (Schiele & Hopps, 2009). Federal funding became more available to schools of social work after World War II and had influence on the curriculum, funding for faculty and financial aid to students.…”
Section: The Profession and The Poormentioning
confidence: 99%
“…Once in rank, new Black faculty members, though few in number, added their voices to the importance and need for greater and non-stereotypical content on racial and ethnic groups. In the second special edition of Social Work, focused on people of color, entitled Racial and Ethnic Minorities, it was reported that some eighty-nine articles were published between 1960 and 1975 that addressed "race relevant questions" (Schiele & Hopps, 2009). Prior to the earlier special edition of social work entitled People of Color (Hopps, 1982), the profession had evidenced some concern about issues relevant to people of color and the articles were generally referred to as "the Negro Problem;" and from 1969 to 1975, as "the Black Phenomenon" (Schiele & Hopps, 2009).…”
Section: The Profession and The Poormentioning
confidence: 99%
“…Yet, concern about the underrepresentation of African Americans and the absence of any focus on race and racial consciousness have been important social welfare themes raised by 19th-century African American scholars in sociology such as W. E. B. Du Bois (Bowles, Hopps, & Clayton, 2016) and 20th-century African American social work scholars such as Hopps (1982), Pinderhughes (1989), and Schiele (Schiele & Hopps (2009). Thus, it is our contention that social work research and practice have ignored these early lessons and have not adequately risen to the call to address these inequalities and the resultant issues that affect African Americans daily.…”
mentioning
confidence: 99%